Diagnostic value of procalcitonin for differentiation between bacterial infection and noninfectious inflammation in febrile children with systemic autoimmune diseases - Sathishkumar Loganathan; Sathish Kumar (Indian Journal of Rheumatology)
Objectives: The objective of this study is to determine the diagnostic value of procalcitonin (PCT) for differentiation between bacterial infection and noninfectious inflammation in febrile children with systemic autoimmune disease. Methods: It was a cross-sectional study and children with systemic autoimmune disease such as systemic lupus erythematosus (SLE) and juvenile idiopathic arthritis (JIA) presenting with fever (>38°C) were recruited. Results: Out of 24 children included, 16 had SLE (11 in disease flare group and 5 in infection group) and 8 had disease flare of Systemic JIA. Two children in SLE infection group died. Mean PCT was 92.2 ng/ml in SLE infectious group and 3.50 ng/ml in SLE flare group which was statistically significant (P = 0.009). However, the mean C-reactive protein was 98 mg/dl in SLE infectious group and 52 mg/dl in SLE flare group which was not statistically significant (P = 0.25). PCT concentration cutoff value >1.2 ng/ml has the sensitivity of 83% (95% confidence interval [CI] 43.6–0.97) and specificity of 72% (95% CI 49.1–87.5), positive predictive value of 50% (95% CI 23.6–76.3) and negative predictive value 93% (95% CI 68.5–98.7). Conclusions: PCT levels >1.2 ng/ml in febrile SLE patients should point to a bacterial infection, whereas PCT levels <1.2 ng/ml might indicate disease flare that could reduce unnecessary antibiotic use. PCT may serve as a useful marker for the detection of systemic bacterial infection in patients with the systemic autoimmune disease.